International Security in the Multipolar Global Order and Russia’s Role in it (Economic and Political Thought, 2013)
The article shows the complex process of building a new, multi-polarinternational order and Russia’s role in it, especially in the field of futurepeace and international security. The author presents many interesting thesesand asks some research questions. For example, he states that the futureinternational system that is being created now will not only have a multi-polarshape but will also be multi-civilizational. He also highlights that, apart fromthe United States and the European Union, Russia will play a very importantrole in the system but only if it becomes a modernized and democratic country.Thus, it is necessary to do everything not to let these entities disappearfrom the political map of the world and make them cooperate in order tostrengthen the peace and international security. In the author’s opinion, inthe nearest future Russia will be forced to cooperate with the Euro-Atlanticsystem and to lead a multi-directional foreign policy, i.e. to cooperation withthe European Union and NATO on the one hand, and with the emergingeconomies, especially China and India, on the other hand. Today, Russianeeds Western technologies and loans as well as Asian markets in order tocarry out necessary modernization and become an important member of the“concert of powers” that will be responsible for the new international systemand its security.